Analysis of Latin American Scientific Production on Academic Performance (2015-2018) - Utrilla Salazar, Dario (2020)
The study describes the characteristics of Latin American scientific production on the variable school performance in journals indexed in Scopus, during the period 2015-2018. A retrospective descriptive study is carried out analyzing 850 articles. It is found that the countries with the highest production are Brazil and Chile. Most of the articles are published in the journals University Training and School and Educational Psychology. It is concluded that Latin American scientific production on academic performance has been increasing progressively in recent years; However, it is still necessary to continue strengthening the dissemination of scientific studies, it is also recommended to use meta-analysis techniques to reach more integrative conclusions that allow us to continue building theoretical knowledge.